Impact of the Four‐Hour Rule/National Emergency Access Target policy implementation on emergency department staff: A qualitative perspective of emergency department management changes. (26th August 2018) - Nahidi, Shizar; Forero, Roberto; Man, Nicola; Mohsin, Mohammed; Fitzgerald, Gerard; Toloo, Ghasem (Sam); McCarthy, Sally; Gibson, Nick; Fatovich, Daniel; Mountain, David; ,
Abstract: Objective: It has been 10 years since the ACEM Access Block Solutions Summit and 5 years since the introduction of the Four‐Hour Rule/National Emergency Access Target (4HR/NEAT) policy. The impact of this policy on ED management and on ED staff has been poorly understood. The aim of the present study was to identify changes in ED management resulting from the policy based on ED staff experiences. Methods: Semi‐structured interviews were conducted and transcribed, imported to NVivo 11 and analysed using a combination of content, thematic analysis and phenomenological focus within a theoretical framework known as the 'logic model'. Results: One hundred and nineteen ED staff participated in 2015–2016 to assess the impact of the policy implementation. Participants were drawn from 16 EDs in New South Wales, Queensland, Western Australia and Australian Capital Territory. In relation to ED management, three themes were identified: changes in ED management; activities and changes driven by the hospital in relation to 4HR/NEAT; and participant experiences in relation to policy compliance by staff. Conclusions: Policy implementation is a complex process that had both positive and negative consequences on how ED staff managed the implementation of the 4HR/NEAT policy and how it changed their work environment. Understanding the perceptions of staff involved in policy implementation has significance for the design of future implementation strategies. The biggest insight from the present study is that ED management is very complex and the policy generated multiple positive and negative changes demonstrating the wide range of processes involved in this area of health services research.